2017
DOI: 10.1089/acm.2016.0135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yoga on Heart Rate Variability and Depressive Symptoms in Women: A Randomized Controlled Trial

Abstract: A 12-week yoga program was effective in increasing parasympathetic tone and reducing depressive symptoms and perceived stress in women with elevated depressive symptoms. Regular yoga practice may be recommended for women to cope with their depressive symptoms and stress and to improve their HRV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 37 publications
2
45
0
2
Order By: Relevance
“…Both physical activity and yoga ameliorate depression (Chu et al 2017). Helgadóttir et al (2016) found that yoga and aerobics are about equally effective on easing the symptoms of depression.…”
Section: Relieving Depression and Anxiety Symptomatologymentioning
confidence: 99%
“…Both physical activity and yoga ameliorate depression (Chu et al 2017). Helgadóttir et al (2016) found that yoga and aerobics are about equally effective on easing the symptoms of depression.…”
Section: Relieving Depression and Anxiety Symptomatologymentioning
confidence: 99%
“…Of the articles reviewed, the majority depicted 12-week long studies that examined the efficacy of yoga in regards to anxiety and mood disturbance. One specific article details not only the effect of yoga on mood, but also the effect of yoga on heart rate (Chu et al 2017). Knowing the relationship of the body and mind it was an expected finding when it comes to the effect of yoga on the cardiovascular system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…9 From the ordinary yoga program, participants were instructed to maintain their concentration and synchronize their breaths with movements during the yoga session. 5 From the benefit of LU meridian (Tables 4 & Table 5), it could be related to the breathing practice in all of yoga lesson. According to the TCM theorem, the meridians HT and PC relate to the heart function and also blood governed by the heart, which flows all over the body, particularly that part of blood serving as the basis for the physiological activities of the heart, including mental activities reflecting its physiological and pathological conditions.…”
Section: Bmentioning
confidence: 99%
“…4 Regular yoga practice may be recommended for women to cope with their depressive symptoms and stress and to improve their heart rate variability (HRV). 5 Evidence is accumulating that yoga improves blood pressure (BP) control, with downregulation of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS). 6 By integrating yoga in therapy can be created to overcome existing impediment in current psychotherapy.…”
Section: Introductionmentioning
confidence: 99%